MOBILE-BASED OUTPATIENT QUEUE SYSTEM USING THE PRIORITY SCHEDULING AND FIRST COME FIRST SERVED SCHEDULING METHOD - Anton Setiawan Honggowibowo; Dwi - Nugraheny; Saprudin - - (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2019)
The outpatient queue system at the Pratama Clinic still uses manuals so that it can implement computerized technology (mobile) to improve health services for patients. In making this outpatient queue system application using the Priority Scheduling method which is a priority scheduling algorithm. Each process is equipped with a priority number (the smallest integer value is usually the biggest priority). This outpatient queue system is mobile based with the aim that patients can register online. Test results using a comparison of smartphones from the Android 4.1 version of Jelly Bean to the Android 7.0 version of Nougat can run. Comparison of distances in applications with google maps, get the same results and test application users using a questionnaire that is calculated with a Likert Scale to get 81.8% results including the "Very Good" category.